Effects of Arousal, Dominance, and Their Interaction on Pleasure in a Cultural Environment. Issue 8 (August 2014) - Miniero, Giulia; Rurale, Andrea; Addis, Michela; Colbert, François
ABSTRACT Being typically hedonic, arts and culture by definition provide pleasurable experiences that are consumed for their own sake. If pleasure acts as the key emotion in these experiences, at the same time other emotions might be elicited by the rich and holistic environment and the interaction that takes place between the cultural product and the consumer. By adopting the common theoretical framework of the PAD model (Mehrabian & Russell, 1974), but innovating in the structural links among the three main affective dimensions—pleasure, arousal, and dominance (PAD)—this study empirically tests whether arousal, dominance, and their interaction generate pleasure. Findings show that arousal and dominance affect pleasure positively and significantly, whereas their interaction affects it negatively. Pleasure leads to a direct and positive effect on satisfaction that mediates a positive effect on behavioral intention.